2022
DOI: 10.2147/ijgm.s375761
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Clinical Significance, Immune Infiltration, and Regulation Network of miR-3940-5p in Lung Adenocarcinoma Based on Bioinformatic Analysis and Experimental Validation

Abstract: Background Based on bioinformatics analysis and experimental validation, we investigated the expression, clinical significance, immune infiltration, and potential signaling pathways of miR-3940-5p in lung adenocarcinoma (LUAD). Methods 521 LUAD tissue samples and 46 normal lung tissue samples from The Cancer Genome Atlas (TCGA) database. We evaluated the relationship between clinical features and miR-3940-5p expression using Kruskal–Wallis, Wilcoxon sign-rank, and logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(57 reference statements)
0
1
0
2
Order By: Relevance
“…Nonetheless, our study and other studies have reported that black patients with lung cancer experienced worse survival rate than white patients [ 49 , 51 ]. Some evidence indicates that white patients may have a worse survival rate [ 52 ]. The great differences in smoking prevalence and hospital choices between black and white patients may partly explain these differences [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, our study and other studies have reported that black patients with lung cancer experienced worse survival rate than white patients [ 49 , 51 ]. Some evidence indicates that white patients may have a worse survival rate [ 52 ]. The great differences in smoking prevalence and hospital choices between black and white patients may partly explain these differences [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tus, we took the AJCC-T stage into account for the construction of the nomogram to avoid any inappropriate exclusion of this variable. In 18) 4638 (30) 1032 ( 7) 1688 (11) 294 ( 2) 582 ( 4) 74 (0) 14259 ( 91) 15590 ( 100) 8630 ( 55) 11444 ( 73) 4488 ( 29) 6353 (41) 1487 ( 10) 2856 ( 18 100) 494 ( 40) 675 (54) 246 ( 20) 352 (28) 100 ( 8) 162 ( 13) 26 ( 2) 3669 ( 72) 5109 ( 100) 1894 ( 37) 2680 (52) 985 ( 19) 1361 ( 27) 335 ( 7) 629 ( 12) 92 ( 2) 7340 ( 75) 9762 ( 100) 3877 ( 40) 5373 (55) 1931 ( 20) 2776 (28) 628 ( 6) 1211 (12) 159 ( 2) 7378 ( 72) 10200 ( 100) 3720 ( 36) 5306 (52) 1754 ( 17) 2593 (25) 563 ( 6) 1096 (11) 131 ( 1) 3051 ( 63) 4862 ( 100) 1408 ( 29) 2048 (42) 604 (…”
Section: Discussionunclassified
See 1 more Smart Citation